Patterns of Sleep and Napping in Saudi Arabia: A Cross-sectional Evaluation - Ahmad A. Bamagoos; Ammar A. Altayeb; Haneen Fayez Rawas; Samirah Sameer Alsulaimani; Mohammed A. Basurrah; Salih A. Aleissi; Siraj O. Wali (Saudi Journal of Medicine and Medical Sciences)
Objectives: Most people in Saudi Arabia reside in population-dense cities and may be predisposed to poor sleep quality. This study aimed to determine the self-reported sleep and napping patterns in a convenient cross-sectional sample of adults living in Saudi Arabia. Materials and Methods: In this cross-sectional study, information related to sleep quantity and quality during workdays and weekends were collected from adults living in four major cities of Saudi Arabia: Makkah, Jeddah, Riyadh and Taif. Demographic, anthropometric, behavioral, socioeconomic, and comorbidity status were also collected. Standardized tools for screening common sleep complaints (i.e., the Epworth Sleepiness Scale, the Insomnia Severity Index, and the STOP-BANG questionnaire) were included. Results: Participants (N = 1200; 40% males) had an average age of 35 ± 14 years. The most common sleep onset-time during workdays and weekends was 12 am. The most common wakeup times during workdays and weekends were 6 am and 12 pm, respectively. There was a significant difference between workdays and weekends in nighttime sleep duration (7.1 ± 2.3 hours vs. 8.5 ± 2.2 hours, P <0.001) and total sleep duration over 24 hours (8.7 ± 2.2 hours vs. 9.7 ± 2.5 hours, P <0.001). There was a greater proportion of participants who took regular daily naps during workdays compared with weekends (51% vs. 33%, respectively, Chi-square test P <0.001). Nap duration during workdays and weekends was similar (2.1 ± 1.1 hours vs. 2.0 ± 1.0 hours, dependent t-test P = 1.0). Conclusion: People living in Saudi Arabia tend to sleep late and have a short nighttime sleep duration and regular long daytime napping. On weekends, these variables change toward the recommended range (i.e., increased nighttime sleep duration and decreased napping count and duration).